Quantitative documentation of traditionally used medicinal plants and their significance to healthcare among the Mishing community of Northeast India - Borah, Dipankar; Mipun, Puranjoy; Sarma, Jintu; Mili, Chiranjib; Narah, Deiji (Ecological Questions, 2021)
Mishing community is one of the major tribal communities residing in Northeastern India. They have adapted their lifestyle with one of the adverse conditions and their reliance on plants for food and medicine is widely prevalent. This article presents an explorative ethnobotanical survey on documentation of plants used by the Mishing community of Assam in treating the common ailments as well as their mode of preparation and administration. Research was conducted in eight villages from four districts of Assam. Various participatory interaction methods, group discussions and semi-structured questionnaires were conducted with a total of 80 respondents. Plant importance analysis was done using four quantitative indices (Use value, Use report, Informant consensus factor and Fidelty level). In total, 153 plants under 126 genera and 62 families are recorded. Fabaceae (11 spp.) was the most dominant family and Clerodendrum and Solanum (5 spp. each) were the most dominant genera. The highest use values were recorded for Musa balbisiana (0.087) followed by Paederia foetida (0.075). Kidney stone has the highest Informant Consensus Factor value of 0.97 with 74 use reports for 3 species. A total of 7 species were found to have ≥ 90% Fidelty Level and Cissus quadrangularis recorded the highest value, i.e. 93.7% FL for treating bone fracture with 75 use reports. In addition, a review of ethnomedicinal plants published in earlier literature for the community is presented, and 77 plants are reported as new ethnomedicinal records for the community. A list of bioactive compounds found in the presently reported plants is also listed. Though modern health facilities have gained pace in the developing countries like India, traditional medicine still co-exists with tribal communities as these are the nearest and reliable forms of treatment in Assam, exemplified by the high degree of reliance on it.